Outcomes of second allogeneic haematopoietic stem cell transplantation in patients with relapse of myelodysplastic syndrome. (2nd April 2019) - Shimomura, Yoshimitsu; Hara, Masahiko; Tachibana, Takayoshi; Ohashi, Kazuteru; Sakura, Toru; Fukuda, Takahiro; Nakazawa, Hideyuki; Iwato, Koji; Kanda, Yoshinobu; Ikeda, Takashi; Eto, Tetsuya; Kanda, Junya; et al.
Summary: Though second allogenic haematopoietic stem cell transplantation (HSCT) is considered a curative treatment option after myelodysplastic syndrome (MDS) relapse, scant epidemiological data are available. We investigated the outcomes and prognostic factors of second allogenic HSCT in 99 patients with MDS who relapsed after the first HSCT. The median age was 53 years (interquartile; 45–59) and 57 patients (57·6%) were male. Five‐year overall survival was 25·3%. Early relapse (adjusted hazard ratio: 2·78, 95% confidence interval: 1·08–7·21, P = 0·035) and poor performance (3·03, 1·71–5·37, P < 0·001) were associated with a significantly poor 5‐year overall survival compared to the other groups ( P < 0·001).